Ice-stream dynamics of the SW Barents Sea revealed by high-resolution 3D seismic imaging of glacial deposits in the Hoop area - Bellwald, Benjamin; Planke, Sverre; Piasecka, Emilia Daria; Matar, M.A.; Andreassen, Karin (Marine Geology, 2018)
Accepted manuscript version. Published version available at https://doi.org/10.1016/j.margeo.2018.03.002 . Accepted manuscript version, licensed CC BY-NC-ND 4.0. Recent developments in seismic acquisition systems and seismic data visualization have contributed to improve the imaging of seismic geomorphologies over a broad range of topics. This study focuses on a new high-resolution P-Cable 3D seismic cube located in the Hoop area in the SW Barents Sea. The scientific motivations of the study are (1) to document glacial landforms on a meter-scale, (2) to study the link of these landforms with the subsurface, and (3) to understand ice-stream dynamics by detailed interpretation of main horizons, including the seabed, intra-glacial horizons, and Upper Regional Unconformity (URU). The horizons are assessed using the concept of seismic geomorphology, and compared with interpretations derived from conventional 3D seismic and state-of-the-art multibeam echosounder technologies to discuss the benefits and limitations of the different geophysical technologies. A well-defined intra-glacial seismic reflection is imaged in the eastern part of the P-Cable cube. This reflection has an overall NE-trending ridge-shaped morphology, which is up to 50 m high and 5–10 km wide, and interpreted as a shear margin moraine. The top of the moraine displays well-defined iceberg ploughmarks and clear slope failure events along its eastern flank. The seabed geomorphology, which has been directly shaped by glacial processes related to multiple phases of ice streaming, appears to be influenced by the buried shear margin moraine. Mega-scale glacial lineations (MSGLs) indicative of fast-flowing ice streams characterize the seabed west of the moraine. Infilled MSGLs and different sets of iceberg ploughmarks with large berms dominate the seabed geomorphology above the moraine. The seabed east of the moraine, characterized by a smooth morphology and few pockmarks, is inferred to reflect more slowly-moving ice. Not resolved by other geophysical ...